Mariage et sexualité dans les fetwas d’Ibrāhīm Bayyūḍ (1899–1981) - Benkheira, Mohammed Hocine (Studi Magrebini, 2021)
Abstract Ibrāhīm Bayyūḍ is a major figure in both contemporary Algerian Ibāḍism and “reformism”. The study of his fatwas is instructive from this point of view: it can help to better understand the specificities of Algerian Ibāḍism, closely articulated to a “traditional” Berber-speaking society, and inserted in spite of everything into a larger national context. This study can also help to better understand the continuity of a religious culture as well as of an ancient ethical model that the endogenous modernization, which accelerated after Independence, has hardly undermined.
Keywords: Bayyūḍ; Ibrāhīm ibn ʿUmar (1899-1981); Réformisme – Mzab

Algérie. Les ibadites, penseurs de la réforme de l’islam - Sereni, Jean-Pierre (Orient XXI, 2021)
L’historien Augustin Jomier a étudié les évolutions doctrinaires des oulémas ibadites implantés à la fin du XIXe siècle dans les communautés berbères du nord du (...)
Keywords: Réformisme – Mzab

The Politics of Islamic Reform (Iṣlāḥ) in Colonial Algeria: Ibadi Reformism in the 20th Century - Jomier, Augustin (2021)
Keywords: Réformisme – Mzab

Les Oulémas et réformistes musulmans en Algérie : une histoire à redécouvrir (2021)
Les Oulémas et réformistes musulmans en Algérie : une histoire à redécouvrir Charlotte Courreye, Augustin Jomier, Ismaïl Warscheid : trois jeunes historiens nous invitent à redécouvrir l'histoire des oulémas et des réformistes musulmans au prisme de l'histoire plutôt que de l'État.
Keywords: Réformisme – Mzab